The nutritional aspects of oak wood-fired cooked pepper consumption in adiyaman, southeastern anatolia (Turkey) - Sabbag, Cigdem; Akça, Erhan (Progress in Nutrition, 2018)
Bell pepper (Capsicum annuum) is a widely consumed vegetable in many regions of Turkey and Adıyaman (SE Turkey) is one of the leading regions for production and consumption. In Adıyaman, cooked consumption of pepper is preferred, particularly eating oak wood-fired oven cooked pepper is a common ritual in summers. Nutrition analyses in fresh and cooked bell pepper were done to determine the nutrition properties of pepper. Along with plant analyses, soils analyses were undertaken to evaluate macro and micronutrient continuum from soil to plants. It was determined that the most of the macro and micronutrient contents of pepper were within the normal range however, soils’ zinc, calcium, iron and organic matter were low. Contrary to these low values, the high phosphorus level (8.5-9.9 kg.da-1) in both sample areas indicate unbalanced fertilization management in the region. The fat-soluble vitamin E along with water-soluble C, B1, B2, B3, B6 and folate acid content of Adıyaman peppers were higher than reference values that revealed their quality.